Peculiarities of the workplace chemical factors influence on the medical personnel health in the department of anesthesiology and intensive care - Davydova, A.; Kurochkin, M.; Kapustin, S.; Давидова, Анна Григорівна; Курочкін, Михайло Юрійович; Капустін, Сергій Анатолійович (My University, 2021)
The risk of adverse reactions as well as allergic symptoms due to the use of chemicals in the workplace among employees of anesthesiology and intensive care units is very high. The majority of doctors, nurses and nursing assistants in such departments experience physical discomfort during work, and at least a quarter have symptoms of allergic diseases. To prevent the harmful effects of chemical factors on health, the medical staff of anesthesiology and intensive care departments should use all available protective equipment. Failure to comply with this rule can lead not only to an increase in discomfort during and after work, but also to the allergic diseases development.
Keywords: chemicals; medical personnel; allergy; protective equipment